The story of monasticism : retrieving an ancient tradition for contemporary spirituality - Peters, Greg, 1971- (Baker Academic, 2015)
Some evangelicals perceive monasticism as a relic from the past, a retreat from the world, or a shirking of the call to the Great Commission. At the same time, contemporary evangelical spirituality desires historical Christian manifestations of the faith. In this accessibly written book Greg Peters, an expert in monastic studies who is a Benedictine oblate and spiritual director, offers a historical survey of monasticism from its origins to current manifestations. Peters recovers the riches of the monastic tradition for contemporary spiritual formation and devotional practice, explaining why the monastic impulse is a valid and necessary manifestation of the Christian faith for today's church.